Penentuan Komposisi Bahan Bakar Nabati Dalam Bahan Bakar Minyak Campuran Menggunakan Metode Direct Counting C-14 - Sanusi, Neneng Laksminingpuri; Ramadhani, Moch Faizal; Nurfadhlini; Aisyah, Lies (BRIN Publishing, 2021)
The composition of biofuel (BF) in mixed oil fuel (MOF) has been determined using the C-14 direct counting method. Determination of the composition of BF in MOF was carried out by pipetting 10 mL of BBMC into a glass vial and then adding 10 mL of Ultima Gold F (UGF) scintillator solution into it. The vial was shaken so that the mixture became homogeneous and then counted using the Elmer Perkin 2900TR LSC (Liquid Scintillation Counter) for 20 minutes for 30 cycles. The results of the counting are displayed in the form of tSIE (transformed external standard spectrum) and cpm (counts per minute). The results of the analysis show that the value of cpm increases with the increase in the percentage of BF in MOF. The lowest and highest cpm values for gasoline, avtur, and diesel samples were 14.2363 and 62.0343, 10.664 and 44.535, and 9.410 and 61.789, respectively. There is a strong correlation between tSIE and cpm values for gasoline and diesel but not for avtur. The results of the analysis of the test sample indicate that the sample is outside the sample series graph. This direct counting method is expected to be a reference in the BBMC quality test.